Staphylococcus aureus colonization and acquisition of skin and soft tissue infection among Royal Marines recruits: a prospective cohort study. (March 2020) - Jauneikaite, E.; Ferguson, T.; Mosavie, M.; Fallowfield, J.L.; Davey, T.; Thorpe, N.; Allsopp, A.; Shaw, A.M.; Fudge, D.; O'Shea, M.K.; Wilson, D.; Morgan, M.; et al.
Abstract: Objectives: Skin and soft tissue infections (SSTIs) are a serious health issue for military personnel. Of particular importance are those caused by methicillin-resistant Staphylococcus aureus and Panton–Valentine leucocidin (PVL)-positive S. aureus (PVL-SA), as they have been associated with outbreaks of SSTIs. A prospective observational study was conducted in Royal Marine (RM) recruits to investigate the prevalence of PVL-SA carriage and any association with SSTIs. Methods: A total of 1012 RM recruits were followed through a 32-week training programme, with nose and throat swabs obtained at weeks 1, 6, 15 and 32. S. aureus isolates were characterized by antibiotic susceptibility testing, spa typing, presence of mecA/C and PVL genes. Retrospective review of the clinical notes for SSTI acquisition was conducted. Results: S. aureus colonization decreased from Week 1 to Week 32 (41% to 26%, p < 0.0001). Of 1168 S. aureus isolates, three out of 1168 (0.3%) were MRSA and ten out of 1168 (0.9%) PVL-positive (all MSSA) and 169 out of 1168 (14.5%) were resistant to clindamycin. Isolates showed genetic diversity with 238 different spa types associated with 25 multi-locus sequence type (MLST) clonal complexes. SSTIs were seen in 35% (351/989) of recruits with 3 training days lost per recruit. SSTI acquisition rate was reduced amongst persistent carriers (p < 0.0283). Conclusions: Nose and throat carriage of MRSA and PVL-SA was low among recruits, despite a high incidence of SSTIs being reported, particularly cellulitis. Carriage strains were predominantly MSSA with a marked diversity of genotypes. Persistent nose and/or throat carriage was not associated with SSTI acquisition. Putative person-to-person transmission within troops was identified based on spa typing requiring further research to confirm and explore potential transmission routes.